2022
DOI: 10.3389/fpain.2022.947562
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional pain phenotypes after Traumatic Brain Injury

Abstract: More than 50% of individuals develop chronic pain following traumatic brain injury (TBI). Research suggests that a significant portion of post-TBI chronic pain conditions is neuropathic in nature, yet the relationship between neuropathic pain, psychological distress, and somatosensory function following TBI is not fully understood. This study evaluated neuropathic pain symptoms, psychological and somatosensory function, and psychosocial factors in individuals with TBI (TBI, N = 38). A two-step cluster analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 109 publications
0
12
0
Order By: Relevance
“…This is somewhat different than our findings, as a significant portion of our sample described pain in the neck, shoulders, and lower back areas. The heterogeneity of such findings across studies indicates a need for additional large-scale trials examining both the topographical organization and somatic progression of pain in chronic TBI (Robayo et al, 2022). This will allow clinical researchers to develop and refine targeted analgesic therapies that can be used on an individualized basis (Baron et al, 2012; Reimer et al, 2014; Robayo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is somewhat different than our findings, as a significant portion of our sample described pain in the neck, shoulders, and lower back areas. The heterogeneity of such findings across studies indicates a need for additional large-scale trials examining both the topographical organization and somatic progression of pain in chronic TBI (Robayo et al, 2022). This will allow clinical researchers to develop and refine targeted analgesic therapies that can be used on an individualized basis (Baron et al, 2012; Reimer et al, 2014; Robayo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Approved recruitment flyers and a posting on the department website were also used to enlist healthy controls. A recent publication by our laboratory (Robayo et al, 2022) focused on sensory function and the emergence of pain phenotypes, whereas the present article focused on neuropsychological outcomes. The University of Miami Institutional Review Board approved the protocol, and all participants provided written informed consent before study participation.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…The data presented in this article is a subset of a more extensive study involving pain, quantitative sensory and psychological/psychosocial evaluations, and brain imaging in individuals with TBI. Pain, quantitative sensory, and psychological/psychosocial data of this larger cohort have been published (Robayo et al, 2022).…”
Section: Study Participantsmentioning
confidence: 99%
“…Incidentally, more than 50% of individuals with TBI report chronic pain (Lahz and Bryant, 1996;Nampiaparampil, 2008). While pathophysiological mechanisms underlying the development of chronic pain after TBI are not entirely understood, those individuals reporting chronic pain frequently present with a combination of characteristics that resemble those of neuropathic pain conditions, including sensory alterations and psychological comorbidities (Ofek and Defrin, 2007;Widerström-Noga et al, 2016;Irvine and Clark, 2018;Khoury and Benavides, 2018;Bouferguène et al, 2019;Leung, 2020;Robayo et al, 2022). Thus, chronic neuropathic pain can be a consequence of trauma or diseases involving the central or peripheral nervous system, such as TBI (Ofek and Defrin, 2007;Scholz et al, 2019;Robayo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, the experience of chronic pain not only is highly variable, including the type of pain, but also the impact of pain on interference with daily activities or how someone may have benefited from treatment, even if still experiencing chronic pain. Research examining factors such as pain severity and interference in daily life has shown that greater pain severity scores were associated with greater anxiety and higher rates of depression, PTSD, and affective distress scores than those with mild or no neuropathic pain 12. As such, understanding the impact of concurrent chronic pain on psychosocial outcomes may be improved by observing how these relationships differ across salient pain-related factors such as interference.…”
mentioning
confidence: 99%